Pengaruh Word of Mouth dan Brand Image Terhadap Minat Beli Konsumen Secara Online pada Media Instagram Produk Skincare Joar di Pekanbaru - Azzariati Putri; Ainun Mardiah; Kodarni (Al-Manar Journal of Accountancy and Business Studies, 2025)
This study aims to determine the partial and simultaneous influence of word of mouth and brand image on consumer buying interest online on Instagram media of Joar Skincare products in Pekanbaru. The population of this study were consumers who knew and were interested in buying Joar skincare products in Pekanbaru City. Sampling used a purposive sampling technique. The number of samples taken was 96 people. The data analysis technique used was multiple linear regression. The results of the hypothesis test show that Word of mouth has a significant effect on consumer online purchasing interest with a t-value of 6.106> t-table 1.665, with a significant level of 0.000 <0.05, Brand image has a significant effect on the variable of consumer online purchasing interest with a t-value of 4.613> t-table 1.665, with a significant level of 0.000 <0.05. Simultaneously, word of mouth and brand image have an effect on the variable of consumer online purchasing interest with a F-value of 171.755> F-table 3,09, with a significant level of 0.000 <0.05. The magnitude of the influence of word of mouth and brand image on consumer online purchasing interest is 78.7%, while the remaining 21.3% is influenced by other factors not included in the regression model.